Biological, physiological and economic characteristics of Onobrychis chorasanica Bunge ex Bois. (Sainfoin) under sowing conditions - Khojakulov, Davlat; Khaydarov, Khislat; Rabbimov, Abdullo; Mukhimov, Tolib; Matkarimova, Gulnaz; Davronqulova, Farzona; Ochilov, Ulugbek; Alikulov, Begali (Plant Science Today, 2024)
Onobrychis chorasanica Bunge ex Bois. (Sainfoin) is a valuable pasture plant that is resistant to drought, produces high biomass and is not inferior to alfalfa in terms of nutrient content. It is urgent to research the possibilities of cultivation of this plant for the purpose of growing hay in hilly conditions. The presence of nitrogen-fixing Rhizobium bacteria in the roots of plants is important in increasing the fertility of desert soils and this feature increases its role in the creation of artificial grasslands in hilly conditions. In the experiments, it was shown that it is possible to reach 100 % germination by mechanical scarification of the seeds isolated from O. chorasanica pods using sandpaper. Germination of unscarred seeds in field conditions depends on the year and the depth of planting them in the soil. In a dry year, the highest fertility was observed to be 13.3-15.0 % in the options where the seeds were buried at a depth of 3-4 cm, and in years with abundant rainfall, this indicator was 35.3 % in the option where the seeds were buried at a depth of 3 cm. The viability of lawns in the 2nd year of life was 72-95 % in different options. Hay productivity of O. chorasanica was found to be 41 centners per ha in hilly conditions and seed yield was up to 250 kg. The results obtained in the research are promising for the intensification of feed production of O. chorasanica in local conditions. The obtained results serve to increase the biomass yield of pasture plants and the variety of used feeds in farms specializing in animal husbandry.